A simbologia da resistência política no livro do apocalipse : hermenêutica a partir de ap 17,1-18 - Melo, Jair Rodrigues (2013)
This work is about the process of symbolization of resistance present in the book of Revelation. The research analyzes the relationship between the set of symbols used in the book and the political resistance of the Christian community on the oppression of the Roman Empire at the dawn of Christianity. Accordingly, from a bibliographical methodology, this study encourages critical reflection between the text and the context of Revelation, seen as engaged literature with the opposition to oppressive conditions to which many Christian communities were subject. The work is divided into three chapters: the first discusses the socio-historical context of Christian communities that favored the emergence of Revelation. The second is an analysis of the text of Revelation 17,1-18 in terms of exegetical and hermeneutical. Finally, the third discusses the ways in which some symbols are described criticism of the political oppression of the Roman Empire.